Ethical Challenges for Healthcare Practices at the End of Life: Interdisciplinary Perspectives - Seidlein, Anna-Henrikje.; Salloch, Sabine (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents a collection of exclusively selected manuscripts on current ethical controversies related to professional practices from an interprofessional perspective. Insights are provided into the diversity of practices and viewpoints from different countries are merged in a unique way. The book contributes to the debate on social and legal issues regarding end-of-life practices such as organ donation, medically assisted dying and advance care planning. In addition, joint international author groups contributed exclusive chapters about European comparisons on end-of-life topics. The focus on country- and culture-specific aspects broadens the view on key issues and makes the book attractive for an international readership. The variety of approaches and methods used informs and inspires the development of new research and best-practice projects.
Chapter 1. Introduction (Seidlein) -- Part 1. Contexts of Professional Practice at the End of Life -- Chapter 2. Ethics of Uncertainty: a Conceptual Convergency (Camier-Lemoine) -- Chapter 3. The Role of Uncertainty of Death in Palliative Carers (Camier-Lemoine) -- Chapter 4. The Concept of 'Spiritual Care' at the End of Life (Kuhn) -- Chapter 5. The Role of time at the Intensive Care Unit: Empirical Perspectives and Theoretical Considerations (Lonergan) -- Part 2. Professional Standards at the End of Life -- Chapter 6. End of Life Care and Brazilian Medical Ethics Advances (Gryschek) -- Chapter 7. Should the Family be Allowed to Override a Patient's Decision to Become an Organ Donor after Death? (Kyrtata) -- Chapter 8. Comparison of Self-assessed Competencies Regarding End of Life Ethics between Physicians and Nursing Staff - Survey Findings from the Unfallkrankenhaus Berlin (Mues) -- Chapter 9. Blurring boundaries at End of Life (Kaiser) -- Part 3. Treatment Preferences and Professional Companionship at the End of Life -- Chapter 10. Advance Care Planning in Germany (Volmering-Dierkes) -- Chapter 11. Breaking Bad News in Cancer: An Assessment of Maltese Patients' Preferences (Azzopardi) -- Chapter 12. Exploring Palliative Care Referrals for Socioeconomically Disadvantaged Patients: A Systematic Review (French) -- Chapter 13. Professional nurses' role in end of life care - contexts and comparisons (Schnell) -- Part 4. Ethics and (Inter-) Professionalism in Healthcare at the End of Life: A Discussion Paper -- Chapter 14. TBD (Azzopardi).
Keywords: Ethics; Medical sciences; Moral Philosophy and Applied Ethics; Health Sciences